AB0586 Current impact of ethnicity on renal histology and outcome of lupus nephritis. (12th June 2018) - Nossent, J.; Raymond, W.; Kang, A.; Wong, D.; Ognejovic, M.; Chakera, A.
Abstract : Background: Lupus Nephritis (LN) remains a serious complication of Systemic Lupus Erythematosus (SLE) and continuous worldwide demographic changes as well as new mechanistic insights and treatment options necessitate regular updating of our knowledge of LN. Objectives: To investigate the current relevance of demographic, clinical and histological characteristics as outcome predictors in patients with Lupus Nephritis. Methods: A retrospective single centre cohort study of all SLE patients undergoing a first renal biopsy for LN evaluation between 1997–2017 in a metropolitan hospital in Western Australia with a 750.000 catchment area. Demographic, laboratory and treatment data were collected at baseline and at last follow-up using a predefined form and histological findings (ISN class) were re-evaluated. Kaplan Meier survival estimates for patient and renal survival were tested by log-rank test. Results: The final study cohort included 90 SLE patients (age 31.5 years, 88% female, time since SLE diagnosis 0.3 years.) of Caucasian (n=42), Asian (n=30), Aboriginal (n=11) and other ethnicity (n=7, mainly SubSaharan Africans). The annual LN incidence estimate was 0.6/100.000. There were no significant differences across subgroups regarding renal (overall median 14) and nonrenal SLEDAI (median 4) scores, proteinuria (median PCR 300 mg/mmol), presentation with raised serum creatinine (31% overall), anti-dsDNA Ab (89%) or hypocomplementemia (88%) or presence of proliferative (Class III/IV: 66%) or membranous (Class V:19%) LN. Corticosteroid (86%), immunosuppressive (87% overall) and antihypertensive drug (69%) use were similar across ethnic subgroups (all p>0.2). After a mean follow-up of 95 months, eight patients (9%) had died, six (7%) received renal replacement therapy and five (6%) had developed CKD. Five and ten years patient survival was similar for Asian and Caucasian patients (95%) and poorest in Aborigines (81% and 70%) (p=0.016) with no impact of gender, ISN class, full house IF findings or PCR >300. Renal 5 and 10 year survival (endpoint RRT) was 100% for Asian, 100% and 96% for Caucasian vs 86% and 64% for Aborigines(p=0.02). PCR >350 predicted worse renal survival (p=0.03), which was not influenced by gender, increased baseline creatinine, ISN class, A/AC/C subclass or presence of full house IF deposits. Conclusions: Asian patients have similar clinical and histological LN findings and experience equally good renal and patient outcomes as Caucasian patients in Western Australia, where the incidence rate of LN is comparable with Europe. Whether the grim outlook for Aboriginal patients relates to intrinsic differences in LN pathophysiology and/or socioeconomic circumstances deserves further study. Acknowledgements: Supported by an unrestricted grant from the Arthritis Foundation of Western Australia. We acknowledge the contributions to data collection made by Drs Brandon Wong and Kimberly Minats Disclosure of Interest: None declared